2022
DOI: 10.1021/acs.jchemed.1c00621
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Course Content Usage on Student Learning in Upper-Level Chemistry Courses

Abstract: Lecture capture videos were explored as beyond the classroom course materials in upper-level descriptive inorganic chemistry courses during Fall 2017, Fall 2018, and Fall 2020 semesters. Page views data from the learning management system (LMS) Canvas site served as a proxy for course content usage materials such as lecture capture videos. There was a significant increase in page views on the LMS site since lecture capture videos were introduced in the course. On the basis of the page views data, students were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Regarding the integration of diverse teaching resources, another characteristics of the course, the questionnaire participants indicated that this was the element that contributed most to their learning, coinciding with studies that conclude that chemistry learning is favored with the use of specialized resources, such as molecular models, explanatory videos, simulations, , and virtual laboratories. Thus, this study provides evidence of the importance of integrating traditional teaching with computer-based didactic methods in order to connect theory to practice in chemistry courses taught in a theoretical modality.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Regarding the integration of diverse teaching resources, another characteristics of the course, the questionnaire participants indicated that this was the element that contributed most to their learning, coinciding with studies that conclude that chemistry learning is favored with the use of specialized resources, such as molecular models, explanatory videos, simulations, , and virtual laboratories. Thus, this study provides evidence of the importance of integrating traditional teaching with computer-based didactic methods in order to connect theory to practice in chemistry courses taught in a theoretical modality.…”
Section: Discussionsupporting
confidence: 63%
“…These results coincide with other studies in which, with the context-based learning approach, students are able to learn chemistry content sufficiently; 20,29 they develop both argumentative 19 and critical thinking 20 skills, and interest and motivation toward learning are favored. 19,30 Regarding the integration of diverse teaching resources, another characteristics of the course, the questionnaire participants indicated that this was the element that contributed most to their learning, coinciding with studies that conclude that chemistry learning is favored with the use of specialized resources, such as molecular models, 31 explanatory videos, 32 simulations, 33,34 and virtual laboratories. 35−37 Thus, this study provides evidence of the importance of integrating traditional teaching with computer-based didactic methods in order to connect theory to practice in chemistry courses taught in a theoretical modality.…”
Section: Relationships Between the Course Characteristics And Academi...mentioning
confidence: 77%
“…Video-based instruction can facilitate deeper understanding by providing students with the ability to control the pace of their learning, revisiting complex concepts as needed. 50 Pacing control was not possible within the DAL class period for individual students, but they were able to access the videos outside of the class time and preview or revisit the content. Effective practices for enhancing videos include embedding questions within the video, 51,52 having students asynchronously discuss the content with peers and the instructor using a platform like Perusall, 53 and differentiating instruction with targeted feedback using interactive video-enhanced tutorials.…”
Section: New Instructional Formatmentioning
confidence: 99%
“…In a physical chemistry course, for example, instructors describe shifting teaching resources to online modalities and noted a strong level of student engagement during the first half-semester of the pandemic. As time elapsed and additional investigations of student engagement could be devised, it was possible to measure the level of student interaction with online resources . This type of observation can serve as a proxy for categorizing students into high-end users (HEU) and low-end users (LEU) of available resources.…”
mentioning
confidence: 99%
“…As time elapsed and additional investigations of student engagement could be devised, it was possible to measure the level of student interaction with online resources. 6 This type of observation can serve as a proxy for categorizing students into high-end users (HEU) and low-end users (LEU) of available resources. Comparisons of these two groups then allows for a more complete picture of student engagement with materials in upper level courses, one that extends the earlier work.…”
mentioning
confidence: 99%